2012
DOI: 10.1590/s0100-879x2012001000004
|View full text |Cite
|
Sign up to set email alerts
|

Silencing HIF-1α reduces the adhesion and secretion functions of acute leukemia hBMSCs

Abstract: Hypoxia inducible factor-1α (HIF-1α) is an important transcription factor, which plays a critical role in the formation of solid tumor and its microenvironment. The objective of the present study was to evaluate the expression and function of HIF-1α in human leukemia bone marrow stromal cells (BMSCs) and to identify the downstream targets of HIF-1α. HIF-1α expression was detected at both the RNA and protein levels using real-time PCR and immunohistochemistry, respectively. Vascular endothelial growth factor (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…34 It has been shown that silencing HIF-1 α in Jurkat cells significantly decreased their migration and infiltration capacity. 35 In this study, TPL combined with IDA reduced both protein and mRNA levels of HIF-1 α in LSC-like cells (Figures 5b and c). In addition, the expression levels of HIF-1 α downstream genes, such as BNIP3, VEGF and CAIX, were also reduced (Figure 5b).…”
Section: Discussionsupporting
confidence: 53%
“…34 It has been shown that silencing HIF-1 α in Jurkat cells significantly decreased their migration and infiltration capacity. 35 In this study, TPL combined with IDA reduced both protein and mRNA levels of HIF-1 α in LSC-like cells (Figures 5b and c). In addition, the expression levels of HIF-1 α downstream genes, such as BNIP3, VEGF and CAIX, were also reduced (Figure 5b).…”
Section: Discussionsupporting
confidence: 53%
“…For example, HIF-1αhigh-expression-mediated microenvironment hypoxia in MSC is one of the important triggers of the niches tumorous process (37). Hypoxia can not only enhance the adhesion and chemotaxis between LSC and MSC, but also reduce the sensitivity of LSC to chemotherapy drugs (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…For example, HIF-1αhigh-expression-mediated microenvironment hypoxia in MSC is one of the important triggers of the niches tumorous process (37). Hypoxia can not only enhance the adhesion and chemotaxis between LSC and MSC, but also reduce the sensitivity of LSC to chemotherapy drugs (39,40). Down regulated expression of HIF-1αin MSC can improve hypoxia in niches and suppress the activity and invasion of LSC (41).…”
Section: Discussionmentioning
confidence: 99%